2015
DOI: 10.3892/mmr.2015.4091
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid inhibits TPA-induced HL-60 cell differentiation by decreasing cellular H2O2 and ERK phosphorylation

Abstract: Retinoic acid (RA), vitamin D and 12-O‑tetradecanoyl phorbol-13-acetate (TPA) can induce HL-60 cells to differentiate into granulocytes, monocytes and macrophages, respectively. Similar to RA and vitamin D, ascorbic acid also belongs to the vitamin family. High‑dose ascorbic acid (>100 µM) induces HL‑60 cell apoptosis and induces a small fraction of HL‑60 cells to express the granulocyte marker, CD66b. In addition, ascorbic acid exerts an anti‑oxidative stress function. Oxidative stress is required for HL‑60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…63 TPA also stimulates in vitro differentiation of monocytoid cells [64][65][66] although the possible underlying mechanisms have not been explored. Thus, we investigated whether TPA could activate autophagy in THP-1 cells during their in vitro differentiation and found that it induced autophagy in these cells, as LC3-II increased and SQSTM1 decreased after 48 h of treatment (Fig.…”
Section: Kshv Decreases Tpa-induced Autophagy In Thp-1 Cells Reducinmentioning
confidence: 99%
“…63 TPA also stimulates in vitro differentiation of monocytoid cells [64][65][66] although the possible underlying mechanisms have not been explored. Thus, we investigated whether TPA could activate autophagy in THP-1 cells during their in vitro differentiation and found that it induced autophagy in these cells, as LC3-II increased and SQSTM1 decreased after 48 h of treatment (Fig.…”
Section: Kshv Decreases Tpa-induced Autophagy In Thp-1 Cells Reducinmentioning
confidence: 99%
“…In cytokine‐activated endothelial cells, VitC inhibited NF‐κB activation which was mediated through inhibition of IκBα kinase by DHA [28]. Low‐dose VitC was reported to inhibit the phorbolester‐driven differentiation of myeloid HL‐60 cells, associated with the inhibition of ERK phosphorylation [29]. On the other hand, VitC activates the JAK2/STAT2 pathway when VitC is taken up via the SVCT2 transporter [30].…”
Section: Introductionmentioning
confidence: 99%
“…HL-60 cells, which are human AML cells, have been used as an excellent model for HL-60 cell differentiation by chemotherapeutic agents. HL-60 cells can be induced to differentiate into granulocytes, monocytes, and macrophages by several agents, such as retinoic acid (RA), ascorbic acid (vitamin C), vitamin D, and 12-O-tetradecanoyl phorbol-13-acetate (TPA), respectively (Zylber-Katz and Glazer 1985; Trayner et al 1998; Yiang et al 2015). TPA decreased the number of myeloblasts and relieved remissions in some of the patients (Han et al 1998).…”
Section: Introductionmentioning
confidence: 99%